Individual Diversity and the Gini Decomposition - Ceriani, Lidia; Verme, Paolo (World Bank, Washington, DC, 2014)
The paper defines the Gini index as the sum of individual contributions where individual contributions are interpreted as the degree of diversity of each individual from all other members of society. Among various possible forms of individual contributions to the Gini found in the literature, the paper shows that only one form satisfies a set of desirable properties. This form can be used for decomposing the Gini into population subgroups. An empirical illustration shows the use of this approach.